Flipping exciton angular momentum with chiral phonons in MoSe2/WSe2 heterobilayers. (14th August 2020) - Delhomme, A; Vaclavkova, D; Slobodeniuk, A; Orlita, M; Potemski, M; Basko, D M; Watanabe, K; Taniguchi, T; Mauro, D; Barreteau, C; Giannini, E; Morpurgo, A F; et al.
Abstract: Optical selection rules in monolayers of transition metal dichalcogenides and of their heterostructures are determined by the conservation of the z-component of the total angular momentum—J Z = L Z +S Z – associated with the C3 rotational lattice symmetry which assumes half integer values corresponding, modulo 3, to distinct states. Here we show, based on polarization resolved and low temperature magneto-optical spectroscopy experiments, that the conservation of the total angular momentum in these systems leads to a very efficient exciton-phonon interaction when the coupling is mediated through chiral phonons. We identify these phonons as the Γ point E" modes which despite carrying angular momentum ± 1 are able to induce an excitonic spin-flip of ∓ 2 thanks to the C3 symmetry. These experiments reveal the crucial role of electron-phonon interaction in the carrier dynamics of group 6 transition metal dichalcogenides.